Language Disorders Suffered by Cerebral Palsy Character in “Margarita, with a Straw” Movie - Melani, Dian Angga; Sukarini, Ni Wayan; Beratha, Ni Luh Sutjiati (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
This research entitled “Language Disorders Suffered by Cerebral Palsy Character in Margarita, with a Straw Movie” was conducted to analyze language disorders in Cerebral Palsy. Seeing language and communication is crucial therefore this research is proposed to identify types of language disorders and their impacts on communication quality. The data of this were the utterances of a Cerebral Palsy character named Laila. This research used the language knowledge theory proposed by Carroll for examining language disorder types and the Communication Function Classification System by Hidecker et al for analyzing the effect of language disorders on communication quality. The data were analyzed by using the observation method and techniques of check, re-check, and cross-check where all data findings were observed, noted, and check properly then presented through words. From the analysis, Laila experienced; 66% phonological disorders where she stuttered and misarticulated words; 20% syntactic disorders where she forgot to use the auxiliary verb to be; 8% semantics disorders in which she uttered an idea that was not in accordance with the topic of discussion; and 6% pragmatics disorders whereas she gave irrelevantly and informatively answers. Her communication quality is level 4 where the phonological disorders greatly affect communication because people were difficult to understand her speech. Thus, the communication did not run effectively and efficiently. Keywords: Language Disorder, Cerebral Palsy, Communication